Adult Education in Italy at the turn of XX and XXI century - Olga Czerniawska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2014)
Italy among developed countries, has one of the lowest levels of education of the population. After World War II the government led the fight against illiteracy, which was common especially in the south and on the islands. Adult education includes the socalled priority groups. In addition to juvenile there are prisoners and foreigners. However, the decision about learning in institutions is not easy. In many cases, the start of education is accompanied by expectations of better professional and social position, better pay. There also remains a question (uncertainty) when to start ?, where to start?, what to learn? Currently in Italy is conducted a discussion on the integration of adult education. It is necessary to develop an integrated program covering different groups: a high level of education, well prepared for lifelong learning (including the Internet), a low level of education, which (despite a) deal with the choice of learning opportunities and the weakest - requiring support and assistance in the choice of courses, training and in their follow-up. Adult Education in Italy is characterized by an individual approach to its participants can talk about education through settlement and choice. The base of the action is unit with its problems, needs, expectations and interests. Research on education reveal the role of groups involving individuals with similar interests, needs and abilities. These groups become the basis for the development of educational projects and programs of work. Adult education institutions are mainly Permanent Education Centres (Centro educazione permanente) in different localities. An important role is played by the Provincial Adult Education Centres (Centri Provinciali per L'Istruzione degli Adulti), Universities of the Third Age and the library.